The impact of the activities of the national poverty reduction strategy On achieving the sustainable development goals An applied research in the Ministry of Labor and Social Affairs (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The objective of the research is to shed light on the nature of the impact of the activities of the national strategy for poverty alleviation in achieving the goals of sustainable development, and the research problem was represented by Is there an effect of the activities of the national strategy for poverty reduction in achieving the goals of sustainable development? and represents the field of research in the Ministry of Labor and Social Affairs For the years (2012-2016) and the results of the sustainable development goals indicators for the years (2012-2016), the ready-made statistical program (SPSS ver.10) was used to calculate the percentages, multiple linear regression equation, the F test and the R2 coefficient, and the research reached a set of conclusions Of the most prominent A There is an effect of the Ministry's research activities in the field of poverty alleviation in achieving the goals of sustainable development, which reached (60%), but that strategy was not supported due to the poor level of implementation, and the most prominent findings of the research from the recommendations is focusing on achieving the next strategies for its goals, to support The goals of sustainable development and advancing the reality of sustainable development in Iraq.